DIGITAL TRANSFORMATION IN EDUCATION AND ITS ROLE IN THE DEVELOPMENT OF THE EFFICIENCY OF EDUCATIONAL INSTITUTIONS AND IN THE ENHANCEMENT OF THE QUALITY OF THEIR OUTPUTS - Leila Idiou; Sara Djabri (International Journal of Innovative Technologies in Social Science, 2025)
This paper takes a close look at the idea of education that relies on digitalization. It treats it as a modern solution — and in some ways a fresh approach — within today’s educational methods. The main goal here is to make clear the very central role that digital transformation plays in improving how educational institutions work, as well as to show its aims, its main advanatges, and the special features that make it stand out. To do this, the study used a descriptive–analytical method, not just to describe what is happening but also to examine, a bit deeper, the factors behind it. What we found is that adopting digital transformation as a clear strategy has become almost a must for making education better and for getting better results overall. It helps raise the efficiency of teachers and students together — and also makes the work of the institution more effective — while using fewer resources and lowering the cost at the same time.